Mortality from leading non-cumor diseases in the Chornobyl cleanup workers of the accident at CHANPP and residents of radiation-contaminated territories in the remote period after the accident on Chorbyl nuclear power (Environment & Health, 2024)
The purpose of the study: Based on a descriptive analysis, to determine the post-accident changes in the level and structure of mortality of participants in the chornobyl cleanup workers of the accident at the Chornobyl Nuclear Power Plant (ULNA) and residents of RADIATION- contaminated TERRITORIES )residents of the RZT) of Ukraine from the main non-neoplastic diseases depending on age, time since the date of the accident and gender.Materials and methods: Mortality from non-neoplastic pathology in 1986-1987 in ULNA, numbering 64,762, and residents of RZT, numbering 174,860, aged 18-60 on the date of the accident as a result of the accident at the Chornobyl nuclear power plant, was studied based on clinical-epidemiological and dose data of the State Register of Ukraine. Epidemiological, medical-statistical, analytical methods were used during the research.Research results: On the basis of descriptive analysis, a description of the level and structure of mortality from non-neoplastic diseases of the ULNA and the residents of the RZT was provided, both for the entire post-accident period and for five-year periods. In ULNA, mortality increased with each five-year period and in recent years has increased by 15.7 times compared to the initial period. In residents of the radioactively contaminated territory of Ukraine, the mortality rate increased for 25 years after the accident, with the highest rate in the period 2008-2012, regardless of age, with subsequent stabilization of the indicators.The structure of mortality among participants of the ULNA and residents of the RZT throughout the entire observation period remains unchanged and almost does not differ from the general mortality trends of the population of Ukraine. Diseases of the circulatory system, digestive organs, and respiratory organs are stable in terms of the frequency of the causes of death. Age, sex, and temporal differentiation of mortality, differences in nosological causes among defined categories of victims of the consequences of the accident at the Chornobyl nuclear power plant were revealed.Conclusions: During the post-accident observation period (1988-2017), diseases of the circulatory system, digestive organs, and respiratory organs remained the main causes of mortality in ULNA in and among residents of RZT aged 18–60 on the date of the Chornobyl accident.The dynamics of mortality in ULNA was characterized by growth during the entire period of observation, in residents of RZT – growth over 25 years with subsequent stabilization.It is necessary to take into account during dispensation the revealed features of mortality of ULNA and RZT in order to develop comprehensive measures to reduce the mortality of this contingent.
Keywords: Сhornobyl cleanup workers of the accident at chanpp; residents of radiation-contaminated territories; mortality from non-neoplastic diseases